Discriminating bipolar depression from major depressive disorder with polygenic risk scores. Issue 9 (17th July 2021) - Liebers, David T.; Pirooznia, Mehdi; Ganna, Andrea; Goes, Fernando S.
Abstract: Background: Although accurate differentiation between bipolar disorder (BD) and unipolar major depressive disorder (MDD) has important prognostic and therapeutic implications, the distinction is often challenging based on clinical grounds alone. In this study, we tested whether psychiatric polygenic risk scores (PRSs) improve clinically based classification models of BD v. MDD diagnosis. Methods: Our sample included 843 BD and 930 MDD subjects similarly genotyped and phenotyped using the same standardized interview. We performed multivariate modeling and receiver operating characteristic analysis, testing the incremental effect of PRSs on a baseline model with clinical symptoms and features known to associate with BD compared with MDD status. Results: We found a strong association between a BD diagnosis and PRSs drawn from BD ( R 2 = 3.5%, p = 4.94 × 10 −12 ) and schizophrenia ( R 2 = 3.2%, p = 5.71 × 10 −11 ) genome-wide association meta-analyses. Individuals with top decile BD PRS had a significantly increased risk for BD v. MDD compared with those in the lowest decile (odds ratio 3.39, confidence interval 2.19–5.25). PRSs discriminated BD v. MDD to a degree comparable with many individual symptoms and clinical features previously shown to associate with BD. When compared with the full composite model with all symptoms and clinical features PRSs provided modestly improved discriminatory ability (Δ C = 0.011, p = 6.48 × 10 −4 ). Conclusions: Our study demonstrates that psychiatric PRSs provide modest independent discrimination between BD and MDD cases, suggesting that PRSs could ultimately have utility in subjects at the extremes of the distribution and/or subjects for whom clinical symptoms are poorly measured or yet to manifest.